A study on histopathological spectrum of hysterectomy specimens for abnormal uterine bleeding in a tertiary hospital in Madhya Pradesh - Arora, Mamta; Arora, Swati; Chandanan, Ani (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2026)
Background: AUB (abnormal uterine bleeding) impacts the quality of life of women. Leiomyoma and adenomyosis are the most common cause of AUB. For exact diagnosis, histopathological examination of hysterectomy specimen is required. Sometimes in histopathology we find carcinomas and other pathologies. So, it is clear that histopathogical examination of the hysterectomy specimen should always be done. In our study also we had two cases of carcinoma detected on histopathology. Methods: In our study we took 100 patients coming to Obstetrics and Gynaecology department at Sukh Sagar Medical College and Hospital for a period of fourteen months from March 2024 to May 2025. A total of 100 patients of reproductive age group, perimenopausal and post-menopausal women with diagnosis of abnormal uterine bleeding who underwent abdominal hysterectomy were taken. Results: A total of 100 cases were included in our study. Maximum number of patients were in the 36-42 years age group. Heavy menstrual bleeding was the commonest clinical presentation. Leiomyoma in the uterus, chronic cervicitis in the cervix and follicular cysts in the ovaries were the commonest histopathology noted. One specimen showed endometrial carcinoma and one specimen had leiomyosarcoma. Conclusions: The findings in present study emphasise the importance of histopathological examination of all hysterectomy specimens to detect malignancies even in the cases which suggest a benign pathology on preoperative assessment.